Silence in the classroom: unraveling the cultural dynamics affecting participation and critical thinking in Malaysian and Vietnamese engineering education - Ha Van Le (Cogent Education, 2024)
This investigation delves into the comparative reticence and passive participation tendencies among engineering students from Malaysia and Vietnam, challenging the prevailing pedagogical paradigms that prioritize vocal engagement and analytical prowess in educational forums. Through a meticulous phenomenographic qualitative analysis of 16 students from two private tertiary institutions, this study unveils the profound influence of ingrained cultural hierarchies and the authoritative educator archetype on the students’ hesitance to initiate inquiries in academic settings. The findings illuminate the pivotal role of educator responsiveness in either fostering or hindering student engagement and the development of critical analytical faculties. Proposing pedagogical strategies aimed at nurturing an educational milieu conducive to active participation and critical thinking for South East Asian learners, this research extends its implications to a broader academic discourse on culturally responsive teaching methodologies that promote inclusivity and active learning across diverse educational landscapes.